The malleability behind terms referring to common professional roles: the current meaning of “boss” in British newspapers - Rosa Giménez-Moreno; Francisco Miguel Ivorra-Pérez (Quaderns de Filologia: Estudis Lingüístics)
The aim of the present research is to approach the current variation and vulnerability to manipulation of concepts, apparently clear and unambiguous, related to usual professional roles. The study concentrates on semantic frames, and subsequent, cognitive models associated to the term ‘boss’ as they are expressed and transmitted through large-scale British media. The qualitative and quantitative linguistic analysis of a substantial corpus of texts, in which this term appears, shows clear differences in its meaning, depending on key factors such as the socio-political and ideological orientation of the medium of publication.